PENINGKATAN MARGIN KEUNTUNGAN: PRAKTIK EFEKTIF JUAL BELI BAHAN BANGUNAN - Rahmatullah, Iqbal; Mariana, Mariana; Armia, Armia (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This research aims to explore the effective practices of buying and selling building materials at the Hidup Subur building shop in Sigli City. The research method used is a qualitative method with the application of field research, which involves interview techniques, documentation and observation to collect data in the field. The research results show that the practice of adding prices in the buying and selling of building materials at the Hidup Subur store creates ethical problems, including price manipulation and non-transparency. Although it provides benefits to sellers and builders, it can be detrimental to homeowners or consumers. It is important to improve transparency, honor initial agreements, and assign responsibility for customer complaints to maintain business ethics. The practice of buying and selling building materials using an additional price system has an impact on all parties involved. Although builders and sellers view it as a common and mutually beneficial practice, homeowners as consumers are sometimes unaware of the added costs. Awareness of this practice needs to be increased, and its ethical and legal aspects need to be further evaluated.